Severe Acute Respiratory Syndrome Coronavirus 2 Viral RNA Load Status and Antibody Distribution Among Patients and Asymptomatic Carriers in Central China - Yuan, Youhua; Wang, Huiling; Zhao, Jing; Jing, Nan; Xu, Junhong; Li, Wei; Ma, Bing; Zhang, Jiangfeng; Li, Gang; Wang, Shanmei; Li, Yi; Wang, Yuming; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
This study aimed to monitor severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) viral loads and specific serum-antibodies (immunoglobulin [Ig] G and M) among confirmed patients and asymptomatic carriers from returning healthy travellers. The throat swabs, sputum, and stool samples from 57 hospitalised coronavirus disease (COVID-19) patients and 8 asymptomatic carriers, among 170 returning healthy travellers were tested using reverse-transcription real-time polymerase chain reaction. SARS-CoV-2 IgM/IgG antibodies were detected via serum chemiluminescence assay. Sequential results showed higher viral RNA loads in the throat, sputum, and stool samples at 3–12 and 6–21 days after symptom onset among severely ill COVID-19 patients. Shorter viral habitation time (1–8 days) was observed in the oropharyngeal site and intestinal tract of asymptomatic carriers. The IgG and IgM response rates were 19/37 (51.4%) and 23/37 (62.6%) among the 29 confirmed patients and 8 asymptomatic carriers, respectively, within 66 days from symptom or detection onset. The median duration between symptom onset and positive IgG and IgM results was 30 (n=23; interquartile range [IQR]=20–66) and 23 (n=19; IQR=12–28) days, respectively. Of 170 returning healthy-travellers to China, 4.7% were asymptomatic carriers (8/170) within 2 weeks, and the IgG and IgM positivity rate was 12.8% (12/94). IgM/IgG-positivity confirmed 3 suspected SARS-CoV-2 cases, despite negative results for SARS-CoV-2 RNA. Compared with other respiratory viral infectious diseases, COVID-19 has fewer asymptomatic carriers, lower antibody response rates, and a longer antibody production duration in recovered patients and the contacted healthy population. This is an indication of the complexity of COVID-19 transmission.